Advancing climate transparency and accountability: TCFD-based climate reporting - Hussin, Nur Syafiqah; Yusri, Yusniyati; Awang, Naqiah; Selamat, Aslam Izah (e-IPH, 2025)
Climate reporting has emerged as a crucial mechanism to scrutinise firms' environmental transparency and accountability, owing to the catastrophic impacts of climate change globally. This study aims to develop a climate-related information disclosure index (CRIDi) that serves as an instrument for a consistent and comparable environmental evaluation for business players in Malaysia. The study’s novelty lies in the integration of the recommendations by the Task Force on Climate-related Financial Disclosures (TCFD) and listing requirements by Bursa Malaysia. It benefits businesses for regulation adherence besides preparing firms to respond timely and appropriately to identified climate risks and opportunities.